Recording the Future: an audio-visual archive of ‘everyday life’ in Indonesia in the 21st century - Hoogenboom, Ireen (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2024)
Recording the Future (RtF) is a long-term project of KITLV (Royal Netherlands Institute of Southeast Asian and Caribbean Studies) in cooperation with PRMB-BRIN (Pusat Riset Masyarakat dan Budaya Badan Riset dan Inovasi Nasional) that has been running since 2003. The project aims to create an audiovisual archive of everyday life in Indonesia during the 21st century that can be used for research, teaching, documentaries, artistic work and so on. Recordings are made every four years in: Jakarta, Delanggu (Central Java), Payakumbuh (West Sumatra), Kawal (on the island of Bintan), Sintang (West Kalimantan), Bittuang (Tana Toraja on Sulawesi), Ternate, and Surabaya. Because the same locations are being revisited, visual changes, continuities in the landscape, and developments in society can be traced and compared over time. The archive consists of footage of people and (how they shape) their environment: work, housing, leisure, education, health, politics, government, infrastructure, urban development, mobility, culture, religion and so on. So far, the RtF archive consists of approximately 700 hours of recordings, which have been indexed and made accessible for research. Recording the Future (RtF) merupakan proyek jangka panjang dari KITLV (Institut Kerajaan Belanda untuk Kajian Asia Tenggara dan Karibia) bekerja sama dengan PRMB-BRIN (Pusat Riset Masyarakat dan Budaya Badan Riset dan Inovasi Nasional) yang sudah berjalan sejak tahun 2003. Proyek ini bertujuan untuk menciptakan arsip audiovisual kehidupan sehari-hari di Indonesia selama abad ke-21 yang dapat digunakan untuk penelitian, pengajaran, film dokumenter, karya artistik dan sebagainya. Rekaman dibuat setiap empat tahun sekali di: Jakarta, Delanggu (Jawa Tengah), Payakumbuh (Sumatera Barat), Kawal (di pulau Bintan), Sintang (Kalimantan Barat), Bittuang (Tana Toraja di Sulawesi), Ternate, dan Surabaya. Karena lokasi-lokasi yang sama dikunjungi kembali, perubahan visual, kesinambungan lanskap, dan perkembangan masyarakat dapat ditelusuri dan dibandingkan dari waktu ke waktu. Arsip ini terdiri dari rekaman masyarakat dan (bagaimana mereka membentuk) lingkungan mereka: pekerjaan, perumahan, waktu luang, pendidikan, kesehatan, politik, pemerintahan, infrastruktur, pembangunan kota, mobilitas, budaya, agama, dan lain-lain. Sejauh ini, arsip RtF terdiri dari sekitar 700 jam rekaman, yang telah diindeks dan dapat diakses untuk penelitian.